2011
DOI: 10.1515/bc.2011.066
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative and independent activities of Sgt2 and Get5 in the targeting of tail-anchored proteins

Abstract: TPR proteins modulate the activity of molecular chaperones. Here, we describe the S. cerevisiae TPR protein Sgt2 as interaction partner of Ssa1 and Hsp104 and as a component of the GET pathway by interacting with Get5. The GET pathway mediates the sorting of tail-anchored (TA) proteins, harboring a C-terminal trans-membrane segment, to the ER membrane. S. cerevisiae sgt2Δ cells show partial defects in TA protein sorting. Sgt2 activity in vivo relies on its N- and C-terminal domains, whereas the central TPR dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 18 publications
8
35
0
2
Order By: Relevance
“…Interestingly, the severity of the viability defect for each strain was dependent on the missing protein, as follows: Get3 Ͼ Get5 Ͼ Sgt2. This order was also observed for GFP-Sed5 mislocalization and hygromycin B sensitivity in GET protein-deleted cell lines (17).…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Interestingly, the severity of the viability defect for each strain was dependent on the missing protein, as follows: Get3 Ͼ Get5 Ͼ Sgt2. This order was also observed for GFP-Sed5 mislocalization and hygromycin B sensitivity in GET protein-deleted cell lines (17).…”
Section: Resultssupporting
confidence: 65%
“…Previous studies indicated that the acidic C-terminal DDLD motif of Hsp104 is responsible for its association with other proteins (17). We noted that Ybr137wp also contains an acidic motif, EEDL, in its C-terminal region.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations